ANALISIS KESESUAIAN PERLAKUAN ASET TETAP PADA PT WAHANA INTERFOOD NUSANTARA TBK BERDASARKAN PSAK NO. 16 - Yani, Dhini Dwi (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The company is an entity that carries out certain activities in order to maintain its business continuity. In carrying out its business activities, fixed asset components play an important role in supporting the company's daily activities in producing products. This research was conducted with the aim of analyzing how the accounting treatment of fixed assets at PT Wahana Interfood Nusantara Tbk refers to PSAK No. 16. This study uses a method in the form of qualitative descriptive analysis. The results obtained indicate that PT Wahana Interfood Nusantara Tbk has implemented PSAK No. 16 in the treatment of its fixed assets. This treatment starts from the recognition of fixed assets, to the disclosure of these assets in the company's financial statements.